2016
DOI: 10.1177/1403494816684118
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in the use of alcohol and drunkenness in adolescents: Trends in the Health Behaviour in School-aged Children study in Finland 1990–2014

Abstract: This study suggests that students with low educational aspiration should be the target population for interventions aiming at reducing the alcohol use and drunkenness of Finnish adolescents. In future interventions aimed at reducing heavier drinking, adolescents (especially girls) from less wealthy families should be the first priority. Further studies on trends in socioeconomic differences in alcohol use and drunkenness in adolescence should be conducted using different indicators of socioeconomic status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
(33 reference statements)
1
23
0
2
Order By: Relevance
“…The results consistently show that the prevalence has dropped across social strata, but not necessarily to the same extent. The US study found that the reduction in frequent binge drinking was smaller in low than in high SES groups , while the decline in regular drunkenness in Finland was weaker among girls with low perceived family wealth than among other girls . Moreover, two studies identified small subgroups of youth whose drinking increased since the turn of the century.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results consistently show that the prevalence has dropped across social strata, but not necessarily to the same extent. The US study found that the reduction in frequent binge drinking was smaller in low than in high SES groups , while the decline in regular drunkenness in Finland was weaker among girls with low perceived family wealth than among other girls . Moreover, two studies identified small subgroups of youth whose drinking increased since the turn of the century.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to younger teenagers, the proportion reporting regular drunkenness actually increased among Finnish 18-year-olds in the 2000s [21]. Moreover, a US study of [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] year-olds showed that the younger the age groups, the steeper was the downward drinking trend [48]. Among young adults, the decline in the period 2000-2016 was negligible.…”
Section: Less Drinking Across Age and Gender?mentioning
confidence: 99%
“…Very few studies assessed alcohol consumption behaviors and/or academic performance among university students in Finland. Segregated studies examined some variables in isolation, younger or older age groups, or did not include academic performance, [49][50][51]; included one type of alcohol consumption behavior among medical students only [52]; or were outdated [53]. This is despite that the levels of alcohol consumption in Finland, although close to the OECD average, have increased over the last 30 years [54]; and the prevalence of HED in 2016 among those aged 15-19 years in the population was 31.9% and among drinkers only of the same age was 51.6% [55].…”
Section: Introductionmentioning
confidence: 99%
“…For example, health differences can be seen both globally and between different socioeconomic groups 34,[36][37][38] . Adolescents can have different opportunities in relation to their knowledge, education, social relationships and socio-economic position 29,36,39 . Thus, rights, duties and responsibilities in relation to their health choices need to be examined in relation to their individual situation, as well as, in relation to their wider contextual circumstances.…”
Section: Introductionmentioning
confidence: 99%